Efek Penggunaan Terapi Plasma Konvalesen pada Proses Pengobatan Pasien COVID-19 - Lokat, Rambu Bangi; Riwu, Magdarita; Damanik, Efrisca M. Br.; Setianingrum, Elisabeth Levina Sari (Universitas Nusa Cendana, 2023)
Background :The high number of Covid-19 cases in Indonesia and the world, has forced the government and all health institutions to continue to seek treatment for Covid-19. Treatment for Covid-19 is still being pursued to provide the best therapy for Covid-19 patients, in this effort, one additional therapy is also given, namely convalescent plasma therapy for Covid-19 patients. The efficacy and safety of the use of convalescent plasma is currently still lacking definite evidence, so it is necessary to study the literature to see the results of existing studies to be reviewed Research Objectives : To find out what effects result from the use of convalescent plasma therapy in the treatment process for Covid-19 patients. Methods : This type of research is a literature review research that uses secondary data. Search literature through the PubMed and Google Scholar databases which are then selected according to the inclusion criteria set for review. The search results data obtained 26 journals according to research topics published in 2020-2021. All research results contained in the journal are arranged in a data extraction table. The results of the literature review were analyzed using topics that were in accordance with the objectives of the literature review based on findings from journals. Results : The results of a review of 26 journals on the use of convalescent plasma, found that 16 journals showed a positive effect in the use of convalescent plasma and there was also the use of convalescent plasma which had a negative effect in 10 journals of the review results . Conclusion : The literature review conducted in 26 journals in this study can be concluded that the effects that occur in the use of convalescent plasma therapy can be in the form of positive effects, namely an improvement in the patient's clinical symptoms and negative effects in the form of side effects of therapy and the lack of role of convalescent plasma therapy.